A Fault Detection Method in Photovoltaic Systems Based on the Deficiency Identification Algorithm - K R, Aravind Britto; S, Muthubalaji; Devadasu, Ghanta; R, Sumathi (Al-Salam Journal for Engineering and Technology, 2023)
Solar energy is a kind of renewable energy source, power production, and stored in a battery for energy management systems. Fault identification is the Direct Current (DC) side of a PV (photovoltaic) system, which is difficult to avoid energy loss in such open-circuit and short-circuit-based renewable energy storage systems. Maximum power point tracking is the existing photovoltaic fault identification technique and it mainly improves the maximum Value of Photovoltaic Power at the Output Side. The Proposed Deficiency Identification Algorithm is used to improve the detection rate of fault occurrence in the PV cell. The Deficiency Identification Algorithm is implemented to detect the fault in the PV arrays. The open circuit fault and short circuit faults are the two major faults in the PV arrays. Solar irradiance level and the temperature are the two output characteristics which decide the output of the panel and also force to employ a battery unit that pedals the PV output and is particularly significant for improving energy conversion, voltage losses and improve efficiency.